Gender (sic) Equality (sic) - Martin Sewell (Opticon1826, 2008)
This article is a response to both a Letter to the Editor by Dr Ambily Banerjee (Banerjee, 2007) and the recent UCL Gender Equality Event. Dr Banerjee claimed to be ‘astounded’ to find a ‘glass ceiling’ (sic) within her own discipline, Anatomy. She concludes her letter with, ‘I have never believed motherhood is a valid excuse for not realising one’s potential’. Both points are wrongheaded, and are the result of bogus feminist thinking. Firstly, men and women are different; and secondly, we have evolved ‘as if’ reproduction is the sole goal for which human beings were ‘designed’ and everything else is a means to that end. Feminism not only harms men, but harms women like Dr Banerjee, too (Quest, 1994; Sommers, 1995). Indeed, women are less happy today than they were in the 1970s and ‘the changes brought about through the women’s movement may have decreased women’s happiness’ (Stevenson and Wolfers, 2007).
Keywords: gender equality